Pendekatan Sejarah dalam Studi Islam - Mochamad Afroni (Madaniyah, 2019)
As time went on Islamic studies increased. Islam no longer touches only textual and doctrinal matters, but has become a complex phenomenon. Islam is not just a way of life, Islam has merged into a cultural system towards civilization. Reviewing and approaching Islam is no longer possible from only one aspect, therefore interdisciplinary methods and approaches are needed. In Islamic methodology, history is needed to know the validity of the past, because it is very poor in studying Islamic teachings using the Historical approach. History has even become the object of Islamic studies. Gives importance to the Historical Approach in an Islamic study.